Pendekatan Buddhis terhadap Māra : Dampak Nafsu, Kebencian, dan Delusi dalam Hubungan Interpersonal - Hadi Wijaya Halim; Andika Febrianto (Dhammavicaya : Jurnal Pengkajian Dhamma, 2025)
This research aims to discover the Buddhist strategies of Māra in Buddhism symbolizes desire, hatred, and delusion, which manifest and disrupt interpersonal relationships in daily life. By analyzing how these mental defilements affect human interactions, the author aims to understand better the root causes of conflict and disharmony in relationships. Buddhist teachings offer strategies to overcome the negative influence of Māra, enabling individuals to cultivate healthier, more meaningful, and harmonious relationships. These strategies include developing self-awareness, practicing compassion, and understanding the impermanence of all things. As Buddhists, it is essential to recognize and overcome our internal Māra to improve the quality of interpersonal relationships and achieve emotional well-being.